(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2012)
The global economy is still perplexed with the impact of the recession which started with the sub-prime crisis in the United States and found its way to other developed and emerging economies of the world. The financial meltdown has definitely cast a deep shadow over the Indian financial sector, most significantly the insurance arena which is still not ’recession-proof. Economic growth spurs insurance activities and recession creates manifold problems for the insurance mechanism. Indian Insurance industry follows closely the fortune of the financial sector and is directly influenced by the movements at the macro-economic level. Continued depressed market and resultant decline in premium volumes (and consequently reduced profits) is likely to put pressure on the management of Indian insurance companies. Yet, despite the slowdown, the performance of the Indian insurance sector has shown consistent improvement. With the liberalization of the financial sector in India, the entry of new private players in the Indian insurance segment has helped accelerate the pace of capital deployment. The present study focuses on the stand of Indian insurance industry amidst economic crisis and the unequivocal impact of recession shaping the future of the insurance business in India.